Incidencia del mosaico de la higuera en dos zonas del este de España - Segarra, J.=700 1 Juarez, M.; Castellvell, D.; Achon, M.A.; Medina, V.
(En, Es)
ilus., 18 ref.
Keywords: FICUS CARICA; ACERIA; ACARINA; VIRUS; EPIDEMIOLOGIA; ESPAÑA; HIGO; MOSAICO DE LA HIGUERA